Marketing Strategies for MSME Products in the Digital Era in Soppeng Regency - Andi Jenni Indriakati; Puji Rahmah; Yusmuliani Yusmuliani (GENTARA: management and accounting research, 2025)
This study examines digital marketing strategies employed by Micro, Small, and Medium Enterprises (MSMEs) in Soppeng Regency, South Sulawesi, during the digital era. Employing a qualitative descriptive method with surveys and in-depth interviews, the research reveals that while most MSMEs have adopted digital marketing primarily through social media the implementation remains basic and faces significant internal and external barriers, such as limited digital literacy and infrastructure. The study recommends structured training programs and improved internet access to enhance the digital competitiveness of local MSMEs